Pyrrolidinone-bearing methylated and halogenated benzenesulfonamides as inhibitors of carbonic anhydrases. Issue 2 (15th January 2019) - Vaškevičienė, Irena; Paketurytė, Vaida; Pajanok, Nikita; Žukauskas, Šarūnas; Sapijanskaitė, Birutė; Kantminienė, Kristina; Mickevičius, Vytautas; Zubrienė, Asta; Matulis, Daumantas
Graphical abstract: Abstract: Two series of benzenesulfonamides bearing methyl groups at ortho/ortho or meta/ortho positions and a pyrrolidinone moiety at para position were synthesized and tested as inhibitors of the twelve catalytically active human carbonic anhydrase (CA) isoforms. Observed binding affinities were determined by fluorescent thermal shift assay and intrinsic binding affinities representing the binding of benzenesulfonamide anion to the Zn(II)-bound water form of CA were calculated. Introduction of dimethyl groups into benzenesulfonamide ring decreased the binding affinity to almost all CA isoforms, but gained in selectivity towards one CA isoform. A chloro group at the meta position of 2, 6-dimethylbenzenesulfonamide derivatives did not influence the binding to CA I, but it increased the affinity to all other CAs, especially, CA VII and CA XIII (up to 500 fold). The compounds may be used for further development of CA inhibitors with higher selectivity to particular CA isoforms.